A Narrative Inquiry on Peer Influence and Academic Engagement in the Kathmandu Valley - Pyakurel, Raj Kumar; Paudel, Devi Prasad (The Third Pole: Journal of Geography Education, 2025)
This paper aims to analyze influence of peers on students’ academic engagement from the perspectives of secondary-level learners in the Kathmandu Valley. The relationships students form with their peers greatly influences their academic involvement, both positively and negatively. In secondary schools, strong and positive peer connections play an important role in enhancing students’ academic success. For this purpose, both primary and secondary sources of information were used. Primary data were collected through in-depth interviews and observations of five students from two institutional schools. The findings revealed thatpositive interactions among peers—such as encouraging one another and working together—boosted students’ engagement and confidence in their academics. In contrast, negative peer pressure led to disengagement and lower academic achievement. Learning is essentially a social process, and peers play a significant role in influencing how students learn. The shared emotions, intellectual efforts, and common goals within peer groups contribute to students’ growth in school. Offering support during difficult times, experimenting with various learning methods, and embracing shared values all help shape a student’s educational experience. Additionally, positive peer learning not only improves academic outcomes but also fosters the development of good character in students.